Researching the gender division of unpaid domestic work: practices, relationships, negotiations, and meanings - Warren, Tracey (Wiley, 2011)
The paper focuses on the potential of quantitative research methods for sociologists who research the gender division of unpaid domestic work. To begin, it reflects on the emergence of the sociological interest in unpaid domestic work and identifies an early core concern with making invisible work visible. It is argued that quantitative research methods provide us with the most valuable opportunities for ‘recognising’ unpaid domestic work since they facilitate larger scale representative projects. However the data in most of the large scale surveys are scant, and fail to reflect developments in the conceptualisation of unpaid domestic work. Four areas of concern to contemporary sociology are identified: domestic work practices, relationships, negotiations and meanings. Given the complex questions that these four sub- topics raise, the paper proposes a range of sub-areas as a focus for ongoing sociological research into unpaid domestic work. It is concluded that despite the methodological challenges presented, detailed indicators of the multiple dimensions of unpaid domestic work need to be agreed so that valid information can be collected as routinely in large scale surveys as are those on paid work.